Effectiveness of a Cognitive-Behavioral Program for Male Batterers in the Intimate Partner Relationship - Lúcar Vidal, Fredrik (2021)
The purpose of the research was to verify the efficacy of a cognitive behavioral treatment program with a gender perspective in male batterers in the relationship. The sample of 48 men who were reported for violence against their intimate partner, and also were forced to undergo psychological treatment by court order. Most of them were adults, without a history of serious psychopathology, employed, with a history of violence in their family of origin no alcohol consumption problems, half of them with only primary and secondary education. Assessed before and after treatment with the Conflict Tactics Scale (CTS-2), the Inventory of Distorted Thoughts towards Women and Violence (IPMV) and the Attribution of Responsibility and Minimization Scale (IRM). The data were analyzed with the t-test for related samples, and the effect size measurements were reported using the Delta coefficient of Glass. Therefore, the results show that the treatment program was effective in significantly reducing the frequency of violent behavior, attributions of responsibility, and the cognitive distortions regarding women and violence against women.